Maternal health situation in the empowered action group states: how far we reached: a comparative analysis of national family health survey-3 and 4 - Das, Hrushikesh; Tiwari, Jaya; Jena, Sunita; Sahu, Kushal Kumar (International Journal Of Community Medicine And Public Health, 2021)
Background: Maternal health constitutes the health of women during pregnancy, childbirth, and the post-partum period. India is one the biggest contributor to maternal mortality, among all the states of India, the Empowered Action Group (EAG) states contributes 61.5% of total mortality, keeping in this view the study compared the NFHS-3 and NFHS-4 survey of the maternal health condition of EAG states of India and evaluated the relationship between maternal health status and predictors of EAG states of India in NFHS-3 and NFHS-4. Methods: This cross-sectional study adopted descriptive secondary data analyses of two rounds of nationally representative sample surveys NFHS-3 and NFHS-4. The data were obtained by the demographic and health survey website after proper procedures and compared for various maternal health indicators of EAG states. Results: In this investigation, progress has been observed from NFHS-3 to NFHS-4 however, the progress is very positive promising to growth. Where their full (antenatal care) ANC indicator growth is very steady. Education and domestic violence are still hampering the growth of full maternal health wellbeing. Conclusions: Given the status of maternal health in India and more especially in EAG states, more improvement in the performance of maternal health-related activities is highly necessary for which health system strengthening coupled with strong political will and community mobilization are some of the urgent strategies required in the EAG states. Above all community, awareness has a greater role in improving the health status in these.